Meningkatkan Hasil Pemahaman Materi Menggunakan Metode PBL di Kelas V SDN 05 Koto Rajo - Nurihaji, Nurihaji (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning outcomes of fifth-grade students at SD Negeri 05 Koto Rajo by using the group discussion learning method. The research was conducted in two cycles, each involving one meeting focused on teaching the Qur’an, particularly QS. Al-Ma’un. The results showed that in Cycle I, although there were some challenges such as students’ lack of engagement, there was a significant improvement in learning outcomes in Cycle II. In Cycle II, the classical completeness increased to 75%, with most students becoming more active in discussions and better understanding the material being taught. This study concludes that the group discussion method can enhance students’ learning outcomes and motivate them to be more engaged in the learning process.